#funnypoliticians: How Do Political Figures Use Humor on Twitter? - Mendiburo-Seguel, Andrés; Alenda, Stéphanie; Ford, Thomas E.; Olah, Andrew R.; Navia, Patricio D.; Argüello-Gutiérrez, Catalina (Frontiers in Sociology, 2022)
Social media has increased its popularity among politicians. If they wish to succeed in the political arena, politicians need to present themselves to citizens as attractive individuals through these platforms. This study examined how politicians present themselves using humor on Twitter. We analyzed tweets (n = 6,443) from 27 politicians to determine their use of different types of humor and its relationship with age, gender, or political position. We also present changes in humor use in relation to the publication of a political survey in which politicians who were part of this study were evaluated. Results showed politicians' use of humor is relatively low in frequency and primarily aggressive. Politicians who are male, younger, and in the opposition tend to use more aggressive humor. We discuss the results considering the role of aggressive humor in political messages. Based on the analyses of tweets and the publication of the survey, we propose as a hypothesis for future studies that politicians' use of humor on Twitter could be affected by the publication of these kinds of surveys.